2020
DOI: 10.1029/2019sw002434
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Variations of GPS Amplitude Scintillation for the Polar Region

Abstract: Global Positioning System (GPS) L1 amplitude data, obtained using the Canadian High Arctic Ionospheric Network (CHAIN) during the period 2008–2018, is used to study the seasonal and solar cycle dependence of high‐latitude amplitude scintillation. The occurrence of amplitude scintillation is predominantly confined to the 10–18 magnetic local time (MLT) and 72–87° Altitude‐Adjusted Corrected Geomagnetic (AACGM) sector and is a winter and equinoctial phenomenon. The occurrence of amplitude scintillation shows a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…It also indicates that the scintillations containing some amount of amplitude fluctuation may occur at local daytime or local night. The observation of amplitude scintillations at local daytime during solar maximum agrees with the study conducted of polar cap scintillations by Meziane et al (2020), who found L1 amplitude scintillations primarily occurring on the dayside, and with a solar cycle dependence.…”
Section: Amplitude and Both-phase-and-amplitude Scintillation Eventssupporting
confidence: 90%
“…It also indicates that the scintillations containing some amount of amplitude fluctuation may occur at local daytime or local night. The observation of amplitude scintillations at local daytime during solar maximum agrees with the study conducted of polar cap scintillations by Meziane et al (2020), who found L1 amplitude scintillations primarily occurring on the dayside, and with a solar cycle dependence.…”
Section: Amplitude and Both-phase-and-amplitude Scintillation Eventssupporting
confidence: 90%
“…Extensive variations in the solar wind as well as in the SME index along with several northward‐southward IMF rotations are seen during the selected time interval. While the measured amplitude scintillation index value constantly remains at the background level during the entire interval, the signal phase index experiences the diurnal pattern variations; amplitude scintillation are usually absent during the minimum phase of the solar cycle (Meziane et al., 2020). For both indices, the model (red trace) satisfactorily reproduces all the signal observed features (blue trace).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the solar cycle on ionospheric scintillation is now well established (Aarons et al., 1981; Meziane et al., 2020). During the 11‐years cycle, the ultraviolet radiation intensity emitted by the Sun varies by one order of magnitude.…”
Section: Predictors Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplitude scintillation occurrence in the polar region is very low due to the nature of the scintillation producing irregularities [37]. It is compounded by completed dominance of phase variations due to the problems with the detrending of the phase of the GNSS signal [12,13] to determine the phase scintillation index.…”
Section: Introductionmentioning
confidence: 99%